El modelo de atención del centro infantil del buen vivir Cacique Guaranga de la comunidad Mindina, parroquia Simiatug. Estudio de la metodología aplicada en el componente educativo y el componente participación familiar y comunitaria. - Poaquiza Chimborazo, José Ambrocio (2013)
This Research is conducted about the methodology of the educational component and the component family and community involvement, about to the CIBV “CaciqueGuaranga" Mindina community, Simiatug Parish, Guaranty Canton, Bolivar Province, 2012-2013. The comprehensive development of children/children dependent on physical, environmental, social, biological and psychological factors, such as individual and community. According to the scientific theories stimulation of child development should strengthen the skills and abilities of the areas of language, cognitive, motor and social staff through recreational activities